Colchicine for acute and chronic coronary syndromes. Issue 20 (1st July 2020) - Imazio, Massimo; Andreis, Alessandro; Brucato, Antonio; Adler, Yehuda; De Ferrari, Gaetano Maria
Abstract : Colchicine is an ancient drug, traditionally used for the treatment and prevention of gouty attacks; it has become standard of treatment for pericarditis with a potential role in the treatment of coronary artery disease. Atherosclerotic plaque formation, progression, destabilisation and rupture are influenced by active proinflammatory cytokines interleukin (IL)-1β and IL-18 that are generated in the active forms by inflammasomes, which are cytosolic multiprotein oligomers of the innate immune system responsible for the activation of inflammatory responses. Colchicine has a unique anti-inflammatory mechanism: it is not only able to concentrate in leucocytes, especially neutrophils, and block tubulin polymerisation, affecting the microtubules assembly, but also inhibits (NOD)-like receptor protein 3 (NLRP3) inflammasome. On this basis, colchicine interferes with several functions of leucocytes and the assembly and activation of the inflammasome as well, reducing the production of interleukin 1β and interleukin 18. Long-term use of colchicine has been associated with a reduced rate of cardiovascular events both in chronic and acute coronary syndromes, with an overall good safety profile. This review will focus on the influence of colchicine on the pathophysiology of coronary artery disease, reviewing essential pharmacology and discussing the most important and recent clinical studies. On the basis of current literature, colchicine is emerging as a possible new valuable, safe and cheap agent for the treatment of acute and chronic coronary syndromes.